Entre o amém e o axé: O trânsito religioso de evangélicos rumo às religiões afro-brasileiras no ABCD paulista - Lima, Lídia Maria de (2012)
This research analyzes the religious transit of people who had their religious biography marked by the participation/involvement in evangelical practices and who currently declare themselves practitioners of Candomblé and Umbanda rituals in the ABCD Paulista region. In order to accomplish this research, we interviewed religious leaders who helped us to understand the organization of Umbanda and Candomblé terreiros in the region; we also applied 80 questionnaires in eight terreiros all around the region, in order to understand the socio-economic profile of the participants. During the analyses of the questionnaires, it was verified the occurrence of transit, in an even more intense way among the Umbamba practitioners, and we analyzed the motivations for that religious move, identifying also the gender motivations, besides the relations of symbolic exchange established among the members and the religious institutions. We verified the main evangelical groups in which those religious subjects transited, observing possible resemblances, as well as their moving away from their worship practices and the African-Brazilian worship practices.